Enhancing livelihoods of poor livestock keepers through increased use of fodder - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The project seeks to engage with a wide range of stakeholders to strengthen the capacity of poor livestock keepers to select and adopt fodder options as well as access market opportunities to enable them to improve their livelihoods. Among its targets, it seeks to establish mechanisms for strengthening and/or establishing consortia of players in the livestock/fodder arena to allow small-scale innovations to spread across systems and identify options for getting research off the shelf and into practice including innovative communication strategies and strategies for making changes at farm level to sustainably improve fodder supply.